Influence of organisational culture on the organisational commitment of academic staff of the University of Cape Coast - Kyeremeh, Alexander (University of Cape Coast, 2014)
The main purpose of the study was to examine the relationship between the university’s organisational culture and lecturers’ commitment to the university. A correlational research was carried out using randomly selected academic staff of the University of Cape Coast. The study involved 237 respondents who responded to a self- administered questionnaire. The Cronbach’s alpha was used to test for the reliability of the instrument. The reliability coefficient was 0.80. The statistical tools used in the data analysis were; descriptive statistics such as mean, median, standard deviation. Inferential statistics such as correlation, independent sample t-test, Point-Biserial Correlation, Pearson Product Moment Correlation and Multiple Regression were also used. The best predictor of lecturers’ commitment to the university was support subculture. It was recommended that the university management should do more to ensure that support subculture is sustained, so as to elicit the utmost commitment of the lecturers. The conclusion is that organisational culture has a significant effect on the organisational commitment of lecturers in the university.
x, 149p :,ill